Ekowisata Mangrove Lantebung Di Permukiman Nelayan Kelurahan Bira Kecamatan Tamalanrea Kota Makassar - Dwi Fuji Astuti; Muhammad Syukur; Hamsu Abdul Gani; Abdul Rahman A Sakka; Najamuddin Najamuddin (Universitas Negeri Makassar, 2022)
This study aims to discover 1) determine the role of fishing communities in developing Lantebung Mangrove tourism objects in Bira Village, Tamalanrea District, Makassar City. 2) determine the impact of Lantebung mangrove ecotourism on the lives of fishing communities in Bira Village, Tamalanrea District, Makassar City. The type of research used in this research is descriptive qualitative research method using observation, interview, and documentation techniques. The results of this study indicate that: 1) The role of the community in the development of Lantebung Mangrove Ecotourism in Bira Village, Tamalanrea District, Makassar City has a function based on status and position in the form of the Lantebung mangrove ecotourism management structure, while several roles are carried out by the community, namely the public relations division, ticket division, infrastructure division, cleanliness and conservation division, tour guide division, and security division. 2) The impact of Lantebung mangrove ecotourism on the lives of fishing communities in Bira Village, Tamalanrea District, Makassar City, there are three impacts that are caused by the presence of mangrove ecotourism, namely the social impact on fishing communities occurs a) changes in community attitudes, b) patterns of cooperative relationships, c) patterns fishing community activities, and d) tourist attraction destinations. The economic impact of the existence of mangrove ecotourism is, a) getting business opportunities, b) creating jobs. And the ecological impacts of mangroves are a) resisting abrasion by waves and wind, and b) as a habitat for aquatic and terrestrial biota.